ANALISIS PENGARUSUTAMAAN GENDER DALAM PEMBANGUNAN DAERAH: (STUDI PADA PEMERINTAH KABUPATEN TAPANULI UTARA PROVINSI SUMATERA UTARA) - King, David; Dewi, Suci Prasita (Jurnal Konstituen, 2024)
Gender mainstreaming policies within the North Tapanuli Regency government, as stipulated in Regent Regulation No. 3 of 2019 concerning Gender mainstreaming, are considered inappropriate, especially within the scope of facilities and infrastructure that support work, especially for women. The percentage of female civil servants (PNS) is quite dominant in North Tapanuli but needs to be met with adequate facilities. Thus, this can have implications for peace, public order, and community protection in the North Tapanuli Regency local government. The purpose of this study was to analyze the extent of gender mainstreaming in regional development within the government of North Tapanuli Regency. The research method used in this study is qualitative research that produces descriptive data with an inductive approach, as for data collection techniques through observation, interviews, and documentation. The results obtained in this study are that the implementation of the policy has been running well, as expected so that civil servants in the Government of North Tapanuli Regency can feel a sense of security in expressing their work without being overshadowed by a sense of gender inequality. This is viewed from the human resources sector, namely, the availability of formations has been fulfilled. The employees of the state civil apparatus who oversee the field of gender mainstreaming come from educational backgrounds that are in line with gender mainstreaming, in addition to providing training and lifting knowledge about gender mainstreaming as an added value for Human Resources who are expected to be able to implement these policies within the government of North Tapanuli Regency. However, the sector of non-human resources (infrastructure, facilities, or budget) has been implemented. However, only some indicators are running well, namely in the budget sector, which still needs to be more. This has implications for the availability of facilities and infrastructure that are not gender-responsive, thus hindering the implementation of these gender mainstreaming policies. Keywords: Implementation, Gender Mainstreaming, Regional Development